ANALISIS PENDAPATAN UMKM KULINER DI MASA PANDEMI COVID-19 DI KOTA PONTIANAK (STUDI KASUS UMKM LINGKUNGAN UNIVERSITAS TANJUNGPURA KHUSUSNYA DISEPAKAT 2 DAN JALAN DAYA NASIONAL) - MARIA ULFA (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Income from food-related small and medium-sized enterprises (SMEs) in Pontianak City is the focus of this research (a case study of environmental SMEs at Tanjungpura University, with a focus on Jalan Sepakat 2 and Jalan Daya Nasional). This investigation makes use of a case study approach to qualitative research. In this investigation, the business players of culinary MSMEs and the surrounding MSME community serve as the data source. and evidence gathered by interviews, surveys, and written records. Reducing data, presenting data, and drawing conclusions are all parts of data analysis. Triangulation and other checks against external sources are useful in validating data. This research found that daily average revenue for MSME businesses was between IDR 400,000 and IDR 1,500,000 before to the Covid-19 epidemic. The Covid-19 epidemic caused a precipitous decline in MSME revenue, which now ranges from Rp 150,000 to Rp 900,000. MSME business actors have started to go back to normal since the start of the covid-19 epidemic, and their average daily revenue has increased by anywhere from IDR 600,000 to IDR 2,000,000 as a result. In order to keep selling during the Covid-19 epidemic, merchants have developed a number of strategies for dealing with the challenges they confront. During the Covid-19 epidemic, MSME business players have resorted to a number of lifesaving methods, such as selling online and through mobile devices and lowering inventory or raw materials for daily sales to ensure that all products are sold out on any given day.